A vector-based watermarking scheme for 3D models using block rearrangements. (14th September 2020) - Narendra, Modigari; Valarmathi, M.L.; Anbarasi, L. Jani; Prasanna, D.R.L.
Watermarking schemes help to secure the ownership, authenticity, and copyright-related security issues of electronic data. Digital watermarking is used to enhance the copyright protection of the 3D models thus overcoming the integrity violations. An efficient, robust, semi-blind computationally secure DWT-based watermarking is proposed for 3D models. Firstly, a block segmentation of the vertices is performed on the horizontally or vertically scrambled host 3D model. The secret watermark is embedded into the lower frequency band of each segment using Discrete Wavelet Transform (DWT). The proposed scheme employs block rearrangement to scramble the host 3D model so as to enhance the security and fidelity of the embedded watermark. Reverse scrambling and inverse DWT is accomplished for constructing the watermarked model. Semi-blind extraction process achieved a successful retrieval of the secret watermark from the watermarked 3D model. A simulation study with a variety of 3D models evidenced the performance of the proposed watermarking scheme in terms of geometrical attacks, robustness and degradation affect.